English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Could someone please tell me how to change:

3x - 2y = 6
-x + 3y = -9
4x - 3y = 6
3x + 5y = 12

Into slope intercept form?
Thank You.

2006-10-26 09:26:05 · 6 answers · asked by Brad C 1 in Science & Mathematics Mathematics

6 answers

slope intercept form is in the form of

y=mx+c

where m is equal to the slope

so
y=(3x-6)/2 for the first equation
slope is equal to 3/2
... and so on

2006-10-26 09:29:23 · answer #1 · answered by javaHungerForce 3 · 1 0

Slope intercept form = much love.

The slope intercept form for the equation of a line is given by the equation:
y=mx+b
where m is the slope and b is the y-intercept (hints the name "slope intercept form"). To put an equation in this form, you simply solve for y.

For equation one:
3x-2y=6 Given
-2y=-3x+6 Subtracted -3x from both sides
y=(3/2)x-3 Divided both sides by -2

You can probably get the rest from there.

2006-10-26 09:31:49 · answer #2 · answered by OMG! PANCAKES LOLz! 2 · 0 0

you're effectively given 2 factors in which your line passes, it extremely is sufficient to define a on the instant line. One element you're given explicitly as (2, 4). The x coordinate of your different element is your x intercept. considering that's an x-intercept, the y coordinate of that element is without delay 0. Your 2d element is hence (-2, 0). From those 2 factors, you will come across a slope. Taking your unique element to be one million and your x intercept to be element 2, you get for the slope: m = (y2 - y1) / (x2 - x1) = (0 - 4) / ((-2) - 2) = (-4) / (-4) = one million This slope you could now plug into the element-slope form alongside with the two of your factors (i choose for element one million) to get y - y1 = m * (x - x1) or y - 4 = one million * (x - 2) If we want, we can resolve for y and alter this into slope-intercept form, giving y = x + 2

2016-11-25 22:10:27 · answer #3 · answered by Anonymous · 0 0

3x - 2y = 6
-2y=-3x+6
y=1.5x-3

-x + 3y = -9
3y=x-9
y=(1/3)x-3

4x - 3y = 6
-3y=-4x+6
y=(4/3)x-2

3x + 5y = 12
5y=-3x+12
y=-0.6x+2.4

2006-10-26 09:35:50 · answer #4 · answered by yupchagee 7 · 0 0

It needs to be changed to form y=mx + b.
I get y = 1.5x - 3

2006-10-26 09:37:53 · answer #5 · answered by Hazel 3 · 0 0

Wise guy......trying the easy way out on HOME WORK huh????

2006-10-26 09:35:20 · answer #6 · answered by Anonymous · 0 0

fedest.com, questions and answers